Indonesia's Transformation and the Stability of Southeast Asia - Rabasa, Angel (RAND Corporation, 2001)
Indonesia, the world's fourth most populous country, is undergoing a profound transformation that could lead to a variety of outcomes, from the consolidation of democracy to return to authoritarianism or military rule, to radical Islamic rule, or to violent disintegration. The stakes are high, for Indonesia is the key to Southeast Asian security. The authors examine the trends and dynamics that are driving Indonesia's transformation, outline possible strategic futures and their implications for regional stability, and identify options the United States might pursue in the critical challenge of influencing Indonesia's future course. Steps the United States might take now include support for Indonesia's stability and territorial integrity, reestablishment of Indonesian-U.S. military cooperation and interaction, aid in rebuilding a constructive Indonesian role in regional security, and support for development of a regional crisis reaction force. A continued strong U.S. presence in the Asia-Pacific region will reinforce the U.S. role as regional balancer.